Градот и крвта. Кон Игор Штикс, Столот на Елијах: Qyteti dhe gjaku. Për Игор Штикс, Столот на Елијах - Dimiškovska, Ana; Ahmeti, Xhabir (Identities: Journal for Politics, Gender and Culture, 2007)
Author(s): Ana Dimiškovska | Ана Димишковска Title (Macedonian): Градот и крвта. Кон Игор Штикс, Столот на Елијах Title (Albanian): Qyteti dhe gjaku. Për Игор Штикс, Столот на Елијах Translated by (Macedonian to Albanian): Xhabir Ahmeti Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 367-380 Page Count: 13 Citation (Macedonian): Ана Димишковска, „Градот и крвта. Кон Игор Штикс, Столот на Елијах“, Идентитети: списание за политика, род и култура, т. 6, бр. 2-3 (лето 2007 - зима 2008): 367-380. Citation (Albanian): Ana Dimiškovska, „Qyteti dhe gjaku. Për Игор Штикс, Столот на Елијах“, përkthim nga Maqedonishtja Xhabir Ahmeti, Identities: Journal for Politics, Gender and Culture, Vol. 6, No. 2-3 (Summer 2007 - Winter 2008): 367-380.